The future of learning and teaching in next generation learning spaces - Fraser, Kym, 1958- (Bingley, U.K. : Emerald, 2014)
Typically new generation learning spaces (NGLS) across the international higher education sector are being designed to support a more student-centred approach to teaching, through more active and collaborative learning opportunities, often using new technology (Keppell et al. 2012). However, the promise of NGLS appear to remain unfulfilled. This book takes a futuristic perspective on these unfulfilled promises, bringing to the fore the key elements of learning, teaching, professional development and design. The book addresses the compelling questions of the decade in an effort to help senior university managers think beyond the pedagogies of yesterday in order to maximize the use and design of physical learning spaces for the future. The book is written in four sections: 1) The future of learning spaces in Universities; 2) The future for learning and teaching in NGLS; 3) The future of professional development for teaching in NGLS; and 4) The future for design in learning environments and spaces.
Personalised learning strategies for higher education / Mike Keppell -- Diverse pictures of learning : the hidden work of shaping next generation learning spaces / Barbara White, Greg Williams, Rebecca England -- Keeping pace with the rapid evolution of learning spaces / Anastasia Morrone, Sue B. Workman -- Pedagogies for next generation learning spaces : theory, context, action / Peter Ling, Kym Fraser -- Assessment in next generation learning spaces / Geoffrey T. Crisp -- Spaces for engaging, experiential, collaborative learning in higher education / Roger Hadgraft, Jo Dane -- What does it take to learn in next generation learning spaces? / Rhona Sharpe -- Inclusive practices in academia and beyond / Helen Larkin, Claire Nihill, Marcia Devlin -- Factors that shape pedagogical practices in next generation learning spaces / Nicola Carr, Kym Fraser -- Transition to next generation learning spaces / Cathy Hall-van den Elsen,Tom Palaskas -- A new approach to professional learning for academics teaching in next generation learning spaces / Barbara de la Harpe,Thembi Mason -- Developing the briefing of designing for the learning landscape : Reflections on RMIT (Royal Melbourne Institute of Technology) University of Technology & Design's approach to next generation learning spaces / Leon van Schaik -- Learning space evaluations : timing, team, techniques / Lisa Germany -- Moving from campus to community / Amanda Achterberg -- Transforming the student experience through learning space design / Jennifer Sparrow, Susan Whitmer -- The future of research in next generation learning spaces / Kym Fraser.
Includes index.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Education -- General; Teaching skills & techniques; Education; Classroom utilization; Education, Higher